Comparison of central venous catheter in brachiocephalic vein and internal jugular vein for the incidence of complications in patients undergoing radiology - Azim Motamedfar; Mohammad M Gharibvand; Asadollah Jalil (Journal of Family Medicine and Primary Care, 2019)
Introduction: Central venous catheter (CVC) is an essential part of modern medical care that delivers the drugs, intravenous fluids, and intravenous feeding to the vein. So far, limited studies have been carried out on the brachiocephalic vein (BCV) in adults. This study aimed to compare the CVC in the internal jugular vein (IJV) and BCV in order to ease of access and incidence of complication such as infectious and mechanical complications. Materials and Methods: This clinical trial was performed on 52 patients who underwent BCV and the IJV catheterization. The patients were compared in two groups of IJV and BCV in order to facilitate catheterization and measure the success rate and catheterization-induced complications. The difference between the two groups was analyzed by Independent t-test and Chi-square tests. Results: Overall, 52 patients underwent intravenous catheterization. The success rate of catheterization in the first attempt was 100%. The problems of catheterization procedure in the IJV group (11.5%) were greater than the BCV group (6.6%). There was no significant difference between the two groups regarding the duration of catheterization, pneumothorax, emphysema, hematoma, arterial puncture, infection, and complete thrombosis, whereas the partial thrombosis in the IJV group (30.76%) was significantly (P < 0.05) greater than the BCV group (23.07%). Conclusion: Catheterization in both brachiocephalic and the IJV is an appropriate, highly efficient, stable, and safe procedure and ultrasound-guided catheterization is very reliable and safe method.